An introduction to derivatives and risk management - Chance, Don M.; Brooks, Robert Edwin 1960- (Cencage Learning, 2016)
Gives you an understanding of how derivatives are used to manage the risks of financial decisions. This book is packed with real-world examples while keeping technical mathematics to a minimum. It delivers coverage of options, futures, forwards, swaps, and risk management as well as a balanced introduction to pricing, trading, and strategy